TD-DFT Prediction of the Intermolecular Charge-Transfer UV-Vis Spectra of Viologen Salts in Solution - Giacomo Saielli (Applied Sciences, 2020)
The absorption spectrum of viologen salts in a medium or low polar solvent is an essential feature that influences all its “chromic” applications, whether we are considering thermochromic, electrochromic, photochromic or chemochromic devices. The prediction by quantum chemical methods of such absorption bands, typically observed in the visible range and due to charge transfer (CT) phenomena, is a very challenging problem due to strong solvent effects influencing both the geometry and the electronic transitions. Here we present a computational protocol based on DFT to predict with very high accuracy the absorption maxima of the CT bands of a series of viologen salts in solvents of low and medium polarity. The calculations also allow a clear dissection of the solvent effects, direct and indirect, and orbital contributions to the CT band.